Inhibition of poly(ADP-ribose)polymerase contributes to the reduction of oxidative stress in murine liver under the conditions of experimental endotoxemia - N. H. Hrushka; S. I. Pavlovych; O. A. Kondratska; N. O. Pilkevych; R. I. Yanchii (Zaporozhye State Medical University, 2019)
The aim of the work is to investigate the effect of the enzyme poly(ADP-ribose)polymerase 1 (PARP-1) inhibitor, 4-hydroxyquinazoline (4-HQN), on the state of the pro- and antioxidant system of murine liver, under the conditions of lipopolysaccharide (LPS) induced inflammation. Materials and methods. Systemic endotoxemia was induced by the administration of LPS (E. coli 0111:B4) at a dose of 3 mg/kg intraperitoneally (IP). A solution of 4-HQN was applied IP at a dose of 100 mg/kg an hour before LPS administration. The processes of lipid peroxidation (LPO) have been evaluated by the content of the end products of LPO in liver tissue by their reaction with thiobarbituric acid (TBA). The concentration of reduced glutathione (GSH) in liver was determined by Ellman's spectrophotometric method. The level of ceruloplasmin (CP) in serum was measured by colorimetric method of Ravin using a test kit (JSC Reagent, Ukraine) in accordance with the manufacturer's instructions and expressed in mg/l. Results. It was established that 24 hours after LPS administration the content of TBA-reactive substances (TBARS) in liver tissue significantly increased, that indicates intensification of POL. The level of GSH and the activity of CP in serum significantly decreased under the conditions of LPS action. The use of the inhibitor PARP-1, 4-HQN, during endotoxemia resulted in 1.7-fold decrease in the amount of TBARS in liver tissue (P < 0.05 compared with LPS) and increased significantly the GSH content (2.9-fold, P < 0.05) and the CP (1.2-fold, P < 0.05). Conclusions. The data obtained using murine model of endotoxemia indicate the involvement of PARP-1 in intensification of POL. Pharmacological inhibition of this enzyme contributed to the reduction of oxidative stress in murine liver and improved the state of antioxidant protection of the body, that is, it had a pronounced protective effect during endotoxemia.